Perubahan Kandungan Antioksidan Kacang Gude (Cajanus cajan (L) Millsp.) pada Proses Fermentasi Tempe Gude - Yuni Sine (Jurnal Pendidikan Biologi undiksha, 2021)
Production process of pigeon pea (Cajanus cajan (L) Millsp.) tempeh  follows several treatment including peeled off, soaked, boiled, and fermented which cause changes of the antioxidant content of pigeon pea (C. cajan (L) Millsp.). pigeon pea is used as the main material for tempeh fermentation in this study which aims to analyze the the changes of antioxidant content in pigeon pea during each treatment. Antioxidant content was analyzed by DPPH phytochemical compound qualitative and quantitative detection. During the soaking process, reduction of antioxidant content was observed. Prior to soaking step, pigeon pea had 9,090% of antioxidant content, this reduced to 9,020% after soaking process and decrease further to 6,146% after boiling process and decrease to 3.236% after fermentation process. Gude seed has a fenolik and flavonoid while tempeh gude has saponin and falvonoid. Soaking, boiling, and fermentation process has proven to reduce the antioxidant content of pigeon pea..